2021
DOI: 10.4143/crt.2020.424
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Prognostic Model Based on Four Genes in Asian Patient with Gastric Cancer

Abstract: Gastric cancer (GC) has substantial biological differences between Asian and non-Asian populations, which makes it difficult to have a unified predictive measure for all people. We aimed to identify novel prognostic biomarkers to help predict the prognosis of Asian GC patients. Materials and Methods We investigated the differential gene expression between GC and normal tissues of GSE66229. Univariate, multivariate and Lasso Cox regression analyses were conducted to establish a fourgene-related prognostic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Previous researchers have identified new prognostic biomarkers. The prognostic model established by 4 genes (RBPMS2, RGN, PLEKHS, and CT83) was a reliable tool to predict the OS of GC patients in Asia (32), and this was also consistent with our bioinformatics analysis and experimental results. There are some limitations to our study.…”
Section: Discussionsupporting
confidence: 86%
“…Previous researchers have identified new prognostic biomarkers. The prognostic model established by 4 genes (RBPMS2, RGN, PLEKHS, and CT83) was a reliable tool to predict the OS of GC patients in Asia (32), and this was also consistent with our bioinformatics analysis and experimental results. There are some limitations to our study.…”
Section: Discussionsupporting
confidence: 86%
“…These findings coincided with Chen et al [ 18 ], who reported PLEKHS1 as one of the four genes of the prognostic-protective marker for predicting the overall survival (OS) of GC using univariate, multivariate, and Lasso Cox regression analyses but Zhang et al [ 21 ] showed PLEKHS1 upregulation in the intestinal-type-GC and it was considered as one of a five-gene signature for the disease using The Cancer Genome Atlas (TCGA) database.…”
Section: Discussionsupporting
confidence: 79%
“…The current study aimed to evaluate PLEKHS1, AADAC and CDKN3 gene expressions in GC because they were included in gene-signature for GC in some bioinformatics analysis studies [ 13 , 18 ā€“ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we tested the predictive power of the 9-gene signature alone, and the results showed that it was a great predictor for OS (AUC = 0.765 in the training set; AUC = 0.703 in the validation set). Compared to a 4-gene signature reported by a previous study, our signature acquired a higher level (AUC for OS, 0.765 vs 0.684) [ 19 ]. Furthermore, we integrated the risk score with clinical factors (age, sex, pathological stage) to construct a multivariate Cox regression model.…”
Section: Discussionmentioning
confidence: 58%